Dukungan Sosial Sebagai Variabel Moderator dalam Hubungan Antara Kesejahteraan Psikologis dengan Stress Kerja pada Pekerja Paruh Waktu - Oksa Lawdy Tanjung (Comit: Communication, Information and Technology Journal, 2024)
Every personnel in an organization always wants low work stress in carrying out their duties wherever they are, but there are still not many studies that specifically analyze how the psychological condition of part-time workers is vulnerable to experiencing work stress while working. This study aims to determine whether there is an effect of psychological well-being on work stress with the role of social support as a moderator variable.